Fabrication of cancellous-bone-mimicking β-tricalcium phosphate bioceramic scaffolds with tunable architecture and mechanical strength by stereolithography 3D printing - Zhang, Yihang; Zhang, Qiang; He, Fupo; Zuo, Fei; Shi, Xuetao (Journal of the European Ceramic Society, 2022)
It is highly challenging to fabricate bioceramic scaffolds mimicking architecture and mechanical strength of cancellous bone. Gyroid structure, which is based on triply periodic minimal surface, highly resembles the architecture of cancellous bone. Herein, β-tricalcium phosphate (β-TCP) bioceramic scaffolds with gyroid structure were fabricated by stereolithography (SLA) 3D printing. The SLA 3D printing ensured high precision of ceramic part. The porosity (51–87%), pore size (250 – 2400 µm), pore wall thickness (< 300 µm) and compressive strength (0.6 – 16.8 MPa) of gyroid bioceramic scaffolds were readily adjusted to match various sites of cancellous bone. The gyroid bioceramic scaffolds were more favorable for cell proliferation than the grid-like bioceramic scaffolds. The cancellous-bone-mimicking gyroid bioceramic scaffolds with tunable architecture and mechanical strength were expected to efficiently repair the target bone defects.